2020
DOI: 10.1101/2020.03.17.996314
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An 1,4-α-glucosyltransferase defines a new maltodextrin catabolism scheme inLactobacillus acidophilus

Abstract: The maltooligosaccharide (MOS) utilization locus in Lactobacillus acidophilus NCFM, a model for human small-intestine lactobacilli, encodes a family 13 subfamily 31 glycoside hydrolase (GH13_31), annotated as an 1,6-α-glucosidase. Here, we reveal that this enzyme (LaGH13_31B) is an 1,4-α-glucosyltransferase that disproportionates MOS with preference for maltotriose. LaGH13_31B acts in concert with a maltogenic α-amylase that efficiently releases maltose from MOS larger than maltotriose. Collectively, these two… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…The genes encoding the two enzymes were located adjacently in the genome and were next to a gene encoding GH65-1 maltose phosphorylase, resulting in the formation of PUL-GH13-GH65 in the milk strain CNRZ32. Similar PUL organization was observed in several species in the L. acidophilus group [35]. The PUL was characterized by the release of maltose from maltooligosaccharides through the cooperation of two GH13 enzymes and further phosphorylation of maltose into βd-glucose 1-phosphate and glucose by the GH65 enzyme in L. acidophilus.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The genes encoding the two enzymes were located adjacently in the genome and were next to a gene encoding GH65-1 maltose phosphorylase, resulting in the formation of PUL-GH13-GH65 in the milk strain CNRZ32. Similar PUL organization was observed in several species in the L. acidophilus group [35]. The PUL was characterized by the release of maltose from maltooligosaccharides through the cooperation of two GH13 enzymes and further phosphorylation of maltose into βd-glucose 1-phosphate and glucose by the GH65 enzyme in L. acidophilus.…”
Section: Discussionsupporting
confidence: 64%
“…GH13-5 and GH13-7 included reference maltooligosaccharide/starch degrading enzymes of L. acidophilus [35]. The genes encoding the two enzymes were located adjacently in the genome and were next to a gene encoding GH65-1 maltose phosphorylase, resulting in the formation of PUL-GH13-GH65 in the milk strain CNRZ32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GH1 gene was annotated as a series of β-type glycoside hydrolases, including multiple β-glucosidases, which might contribute to the degradation of β-glycosidic bonds in LJGO. The GH13 gene is an α-type hydrolase with 43 subfamilies, many of which are glucosidases that decompose starchrelated substrates 11 like the main structure in LJGO. However,…”
Section: Discussionmentioning
confidence: 99%
“…We also found that LAB can utilize α-glucans such as short, branched starches containing α-1,4and α-1,6-glucans and maltooligosaccharides that mainly contain α-1,4and branched α-1,6gluco-oligosaccharides. [11][12][13] The glycoside hydrolase family 13 (GH13) of α-glucosidases mainly decomposes α-1,4and α-1,6linked glucose residues and is widely distributed in LAB strains. However, most focus is directed towards the structural characterization of marine glucan and regulation of the gut microbiota structure, whereas the specific mechanisms of action of glucans on microorganisms have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%